Social Interaction Between the Communities of The Ex-East Timor and Local Communities in The Border Areas of Indonesia and the Democratic Republic of Timor Leste in the District of North Central Timor - Binsasi, Heribertus; Seran, Remigius; Nino, Handrianus (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
The focus of the research to be achieved in this simple study is to reveal the patterns of social interaction that exist between local residents and former East Timorese residents who live around the border area. Meanwhile, the final goal sought is how harmonization exists between communities in strengthening national identity as Indonesian citizens or as citizens of the Democratic Republic of Timor Leste who live in Indonesian territory. The method used is qualitative with a cultural study approach, with data collection techniques through observation, in-depth interviews and documentation of local community groups and former East Timorese residents in the border areas of North Central Timor Regency. For data analysis techniques, researchers used interactive model data analysis techniques with data reduction. Based on research results